2018
DOI: 10.1016/j.jpainsymman.2018.04.003
|View full text |Cite
|
Sign up to set email alerts
|

“Suffering” in Palliative Sedation: Conceptual Analysis and Implications for Decision Making in Clinical Practice

Abstract: Palliative sedation is an increasingly used and, simultaneously, challenging practice at the end of life. Many controversies associated with this therapy are rooted in implicit differences regarding the understanding of "suffering" as a prerequisite for palliative sedation. The aim of this study is to inform the current debates by a conceptual analysis of two different philosophical accounts of suffering-1) the subjective and holistic concept and 2) the objective and gradual concept-and by a clinical-ethical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Today it is not clear what 'unbearable suffering' means and when a symptom is considered refractory, particularly in case of existential suffering. [29][30][31] The observation that pain was associated with the use of continuous deep sedation furthermore might explain the age differences we found. Although older patients seem more likely to experience unbearable pain symptoms, previous studies have shown that younger hospitalized patients are more likely to report pain and more likely to receive pain medication.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Today it is not clear what 'unbearable suffering' means and when a symptom is considered refractory, particularly in case of existential suffering. [29][30][31] The observation that pain was associated with the use of continuous deep sedation furthermore might explain the age differences we found. Although older patients seem more likely to experience unbearable pain symptoms, previous studies have shown that younger hospitalized patients are more likely to report pain and more likely to receive pain medication.…”
Section: Discussionmentioning
confidence: 94%
“…Today it is not clear what ‘unbearable suffering’ means and when a symptom is considered refractory, particularly in case of existential suffering. 2931…”
Section: Discussionmentioning
confidence: 99%
“…What are the moral claims of intolerable suffering? [ 4 ]. Bozzaro and Shildmann [ 4 ] argued that the answers to these questions are determined by the underlying assumptions about the nature of suffering.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ]. Bozzaro and Shildmann [ 4 ] argued that the answers to these questions are determined by the underlying assumptions about the nature of suffering. They distinguished two typologies of suffering that form these underlying assumptions: a subjective/holistic one informed by the work of Cassell [ 5 ] and an objective/gradual one informed by the work of van Hooft [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The complex nature of existential suffering (ES)4–7 continues to fuel the controversy about whether it is a main indication for PS or not (especially if physical pain is under control) 8–10. Distinguishing kinds of suffering is problematic in itself, and objective or subjective assessment of different kinds of suffering is a hotly debated topic in the medical literature 11. The definition of ES is elusive, because the boundaries between it and other kinds of suffering (psychological, social and spiritual) are blurred 12.…”
Section: Introductionmentioning
confidence: 99%